Identification of Displaced Endometrial Glands and Embryonic Duct Remnants in Female Fetal Reproductive Tract: Possible Pathogenetic Role in Endometriotic and Pelvic Neoplastic Processes - Bouquet De Joliniere, Jean; Ayoubi, Jean Marc; Lesec, Guy; Validire, Pierre; Goguin, Alexandre; Gianaroli, Luca; Dubuisson, Jean Bernard; Feki, Anis; Gogusev, Jean (Frontiers in Physiology, 2012)
Background: Recent findings strongly promoted the hypothesis that common pelvic gynaecological diseases including endometriosis and ovarian neoplasia may develop de novo from ectopic endometrial-like glands and/or embryonic epithelial remnants. To verify the frequency, the anatomical localization and the phenotype of misplaced endometrial tissue along the fetal female reproductive tract, histological and immunohistochemical analyses of uteri, fallopian tubes, and uterosacral ligaments were performed. Methods: Reproductive organs were collected from seven female fetuses at autopsy, five of them from gestational ages between 18 and 26 weeks and two fetuses with gestational ages of 33 and 36 weeks deceased of placental anomalies. Serial sections from areas containing ectopic glands and embryonic duct residues were analyzed by histological and immunohistochemical procedures. Results: Numerous ectopic endometrial glands and stroma were detected in the myometrium in two foetuses with low levels of expression of estrogen alpha (ER-) and progesterone receptors (PR). The embryonic ducts were localized in the uterine broad and ovarian ligaments and under the fallopian tube serosa in six foetuses. Low levels of steroid receptors expression were found in the embryonic residues, whereas CEA and Ca 125 were not detected. The embryonic residues stromal component strongly expressed the CD 10 and vimentin proteins. Conclusion: The anatomical and the immunohistochemical features of the ectopic organoid structures identified in foetal female reproductive tract suggest that endometriotic as well as neoplastic disease in adult women may develop on the basis of misplaced endometrial glands and/or embryonic cell remnants.